Bipolar gate drive integrated circuit for insulated gate bipolar transistor to achieve better tradeoff between the turn‐off losses and collector voltage overshoot. Issue 5 (1st September 2016) - Zhu, Jing; Zhang, Yunwu; Sun, Weifeng; Lu, Yangyang; Du, Yicheng; Yi, Yangbo
Abstract : A bipolar gate drive circuit considering the mitigation of the turn‐off losses ( E off ) and the overshoot of the collector voltage ( V OV ) for the insulated gate bipolar transistor (IGBT) is proposed with 600 V bulk‐silicon bipolar‐complementary metal–oxide–semiconductor double‐diffused metal–oxide–semiconductor technology. Feature of this study is that a differential output circuit and a self‐adaptive turn‐off gate resistance optimiser are used. By using the differential output circuit, only one power supply is needed to provide the bipolar gate control signal for the driven IGBT. With the proposed optimiser, the turn‐off gate resistance can be self‐adjusted according to the changing rate of the collector voltage (d V CE /d t ) and collector current (d I CE /d t ) during the turn‐off process. Thus, the losses during the d V CE /d t phase and the d I CE /d t phase can be designed independently. Due to that the V OV is only depended on the d I CE /d t, the authors can reduce the V OV by 52% without sacrificing the total turn‐off losses E off and a better trade‐off can be achieved by using the proposed drive circuit, compared with the conventional one. Numerous formula analysis, simulations and experiments are performed to verify the above electrical characteristics.